2009
DOI: 10.1152/ajpheart.00169.2009
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting phosphodiesterase-5 inhibitor, tadalafil, induces sustained cardioprotection against lethal ischemic injury

Abstract: The ability of pharmacological preconditioning mimetics to confer long-lasting and sustained cardioprotection may be a logical criterion to develop a drug that can be used clinically for cardioprotection. We propose here that the use of long-acting phosphodiesterase-5 inhibitor, tadalafil, may confer sustained cardioprotection against ischemia. Tadalafil (5 mg/kg) was administered orally to male C57B/6J mice (n = 6 in each treatment subgroup at each time point studied). Hearts were isolated and subjected to 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
22
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 27 publications
7
22
0
Order By: Relevance
“…More importantly, the cytoprotective effects of one-time treatment of the cells with tadalafil were extended to at least 36 h after treatment. We have already shown in vivo that repeated administration of tadalafil at regular intervals of 48 h extended the cardioprotective effects of tadalafil treatment (2). In the light of these results, our present study extrapolated the prolonged prosurvival and proproliferative effects of tadalafil in MSCs via cGMP/PKG signaling.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…More importantly, the cytoprotective effects of one-time treatment of the cells with tadalafil were extended to at least 36 h after treatment. We have already shown in vivo that repeated administration of tadalafil at regular intervals of 48 h extended the cardioprotective effects of tadalafil treatment (2). In the light of these results, our present study extrapolated the prolonged prosurvival and proproliferative effects of tadalafil in MSCs via cGMP/PKG signaling.…”
Section: Discussionsupporting
confidence: 61%
“…Tadalafil belongs to the group of long-acting PDE5 inhibitors and protects the ischemic heart for extended time duration (2). We have already shown that tadalafil administration reduced left ventricular (LV) end-diastolic pressure and increased LV developed pressure besides reducing cardiomyocyte injury through its cytoprotective effects.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, single-dose administration of the longacting tadalafil was reported to have variable effects on blood pressure. The applied dose of tadalafil, 4 mg/kg via gastric delivery, was approximated from human studies and was reported to reach protective plasma concentrations in rodents (Sesti et al, 2007;Ahmad et al, 2009;Salloum et al, 2009Salloum et al, , 2014Koka et al, 2014). In this study, monotherapy with iNO and TAD or combined application did not compromise blood pressure, one of the most critical parameters during I/R treatment protocols.…”
Section: Discussionmentioning
confidence: 78%
“…Dose and timing of NO inhalation was selected on the basis of previously reported results (Hataishi et al, 2006). Tadalafil (Kemprotec Ltd., Cumbria, UK) dissolved in 30% solution of 2-hydroxypropyl-b-cyclodextrin (SigmaAldrich, St. Louis, MO) was administered via gastric gavage (4 mg/kg) 1 hour prior to I/R, which was determined on the basis of previously reported interspecies dose extrapolations (Ahmad et al, 2009;Salloum et al, 2009;Koka et al, 2010). To determine acute cardiac cGMP responses to myocardial ischemia during different treatment regimens, an additional subset of animals (n 5 6-8 per treatment arm) was euthanized 20 minutes after reperfusion (Fig.…”
Section: Methodsmentioning
confidence: 99%